Reprint of: Impacts of Mayan land use on Laguna Tuspán watershed (Petén, Guatemala) as seen through clay and ostracode analysis. (February 2015) - Fleury, Sophie; Malaizé, Bruno; Giraudeau, Jacques; Galop, Didier; Bout-Roumazeilles, Viviane; Martinez, Philippe; Charlier, Karine; Carbonel, Pierre; Arnauld, Marie-Charlotte
Abstract: Most of the cities built by the Mayas in the Petén area, in the Central Yucatán Peninsula, were abandoned 1200 to 1000 years ago. The phenomenon is sometimes un-appropriately called "the collapse of the Maya civilization". Its main causes are still debated, ranging from climatic according to the occurrence of severe or modest droughts, to societal in the form of environmental mismanagement of the environment. In both processes, it is inferred that stress triggered the formation in many Petén lake sediments of erosional clay deposits, known as 'Maya clays'. This work presents a high resolution, multi-proxy study of 'Maya clays' in lacustrine sediments from Laguna Tuspán, near the archaeological site of La Joyanca. Micropaleontological (ostracodes), mineralogical (clay minerals) and geochemical (bulk elemental composition and stable isotopes in organic carbon) records reveal three different phases of soil erosion throughout the last 5300 years. The oldest phase from 5281 to 2998 cal yr BP (i.e. 3331 - 1048 BC) is characterized by successive natural and moderate soil erosion deposits which follow climatic variations recorded in the American tropical belt. The time interval between 2998 and 1281 cal yr BP (i.e. 1048 BC and AD 661) contains four distinct erosional layers which, according to clay mineralogy, are indicative of both increased erosion of the regolith and strong soil loss. The most recent, also the most massive, deposit of Maya clay ends around 1281 cal yr BP (AD 661), that is some 200 years before the so-called 'Maya collapse' in the Petén area. Recent archeological fieldwork studies indicate that a population mobility took place into the city of La Joyanca from its hinterland by the early Late Classic Period (ca. AD 600), that is, at the end or just after this erosion episode, and well before the occurrence of the Terminal Classic-Postclassic (AD 800-1250) drastic climatic changes. Shifts in environmental management by the local society and timing of urbanization may explain environmental changes better than droughts per se. Highlights: This study provides the first record from Guatemala to include clay mineralogy. Only sediments older than 2998 cal yr BP record climatic trends. Four erosional layers appear after the first Maya settlement in 2900 cal yr BP. Maya agricultural activities led to increasing soil erosion. The last erosional interval ends 200 years before the Classic Maya collapse.